Peran Hukum Dalam Perlindungan Anak dan Pemberdayaan Perempuan Sebagai Upaya Mewujudkan Keadilan Gender di Indonesia - Jainah, Zainab Ompu; Refanza, Dymaz; Aqeel, M Arkan; Ahmad, Alvinzach (Journal of Health Education Law Information and Humanities, 2025)
Law plays a central role in achieving gender justice in Indonesia through child protection and women's empowerment. Children and women are often vulnerable groups facing various forms of discrimination, violence, and social injustice. This article examines how national and international legal frameworks, including the Child Protection Law and various women's empowerment policies, contribute to protecting their rights and promoting gender equality. Through a literature review, the article analyzes the effectiveness of the law in addressing issues such as violence against children, human trafficking, early marriage, and women's access to education, economics, and politics. The discussion also covers challenges to legal implementation, such as weak enforcement, low public awareness, and cultural factors that hinder gender justice. The article concludes that legal harmonization, institutional capacity building, and public education are key to achieving sustainable gender justice in Indonesia.